The Influence of Accrual Earnings Management, Real Earnings Management, and Corporate Governance on Firm Value with Financial Performance as a Mediating Variable: A Study of Manufacturing Companies 2021–2025 - Nurshanti, Riska Baini; Rachman, Andry Arifian (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Earnings management by company management can reduce the quality of earnings information. Meanwhile, the implementation of corporate governance is considered capable of curbing this behaviour. This study aims to analyse the effect of accrual earnings management, real earnings management, and corporate governance on financial performance and firm value, with financial performance as a mediating variable, in 228 manufacturing companies listed on the Indonesia Stock Exchange during the 2021-2025 period. This study uses a quantitative approach based on Partial Least Squares Structural Equation Modelling. The results show that accrual earnings management has a negative but not significant effect on financial performance (O = -0.073; p-value 0.0777), but a negative and significant effect on firm value (O = -0.113; p-value 0.045). Real earnings management has a negative and significant effect on financial performance (O = -0.526; p-value 0.000), but a negative and not significant effect on firm value (O = -0.1096; p-value 0.073). Corporate governance has a positive and significant effect on both financial performance (O = 0.196; p-value 0.000) and firm value (O = 0.096; p-value 0.0099). Financial performance itself has a positive and significant effect on firm value (O = 0.349; p-value 0.000). Financial performance is further shown to fully mediate the effect of real earnings management on firm value and to partially mediate the effect of corporate governance on firm value, but not to mediate the effect of accrual earnings management on firm value.